2021
DOI: 10.1002/mnfr.202001202
|View full text |Cite
|
Sign up to set email alerts
|

Diosgenin Protects Against Kidney Injury and Mitochondrial Apoptosis Induced by 3‐MCPD Through the Regulation of ER Stress, Ca2+ Homeostasis, and Bcl2 Expression

Abstract: Scope Diosgenin (DIO) is a natural steroid sapogenin presented in various plants. It exerts anti‐oxidant, anti‐inflammatory and anti‐diabetic nephropathy properties. The present study evaluates the intervention effect of DIO on nephrotoxicity induced by food contaminant 3‐chloro‐1, 2‐propanediol (3‐MCPD) in vivo and in vitro. Methods and Results Treatment with DIO (15 mg kg−1 d−1) in Sprague‐Dawley rats for 4‐week relieves kidney injury induced by 3‐MCPD (30 mg kg−1 d−1). In vitro, DIO (2, 6, and 8 µM) allevia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…Disruption of ER homeostasis results in accumulation of unfolded and misfolded proteins in the ER, leading to ERS. ERS may cause cell death by inducing Ca 2+ overload, inhibiting protein synthesis and promoting apoptosis [52]. Khaled Elmasry et al…”
Section: Discussionmentioning
confidence: 99%
“…Disruption of ER homeostasis results in accumulation of unfolded and misfolded proteins in the ER, leading to ERS. ERS may cause cell death by inducing Ca 2+ overload, inhibiting protein synthesis and promoting apoptosis [52]. Khaled Elmasry et al…”
Section: Discussionmentioning
confidence: 99%
“…3,5,6,27 Diosgenin (as a phytochemical with multiple biological properties) has shown significant protection against various inflammatory and cardiovascular diseases. 13,15 Recent studies also demonstrate that diosgenin ameliorates dextran sulfate sodium (DSS)-induced colitis in mice through the modulation of gut microbiota and the enhancement of SCFA production. 28 Compared with DSS-induced colon injury, diosgenin improved the colon homeostasis through modulating the gut microbiota, including increases in the relative abundance of several probiotic bacteria, and decreases in the pathogenic bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Diosgenin is a sapogenin and dietary supplement derived from various plants with anti-thrombosis, anti-inflammatory, antioxidant and anti-cancer properties. 13,14 The beneficial effects of diosgenin have been observed in cardiovascular diseases, metabolic diseases, and inflammation. 13,15,16 Recently, a study found that oral administration of diosgenin prevented changes in monocrotaline-induced pulmonary and cardiac pathophysiology in rats.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Secondly, modulators targeting mitochondrial Ca 2+ mediate apoptotic pathways and may also be treatments for kidney disease therapy (Figure 1). Inhibition of ER stress by 4-phenylbutyric acid (4-PBA) and Diosgenin mitigates ER-associated mitochondrial apoptosis by maintaining Ca 2+ homeostasis and mitochondrial dynamics, which ameliorates 3-MCPD-induced kidney injury [105,106]. In addition, 4-PBA also decreases Porcine Circovirus Type 2 (PCV2) infection-induced apoptosis by decreasing the cytosolic and mitochondrial Ca 2+ load in porcine kidney PK-15 cells [107].…”
Section: Targeted Ca 2+ Signaling For Therapy Of Kidney Diseasesmentioning
confidence: 99%